América del Sur en el comercio global (2007-2016) - Fernández Rodríguez, Milú O. V. (2018)
This paper analyzes the main characteristics of the trade of goods and services of South America according the changes in the international context. Mainly, it analyzes the commercial flows, the main commercial partners and the main characteristics of the goods and services marketed. In addition, the analysis is done at the region and country level.